«Service to the Three Saints Mitrofan of Voronezh, Demetrius of Rostov and Tikhon of Zadonsk» by Bishop Jeremiah (Soloviev): the history of the text - M. V. Sidneva (Российский журнал истории Церкви, 2021)
The publication consists of a research article and the first publication of the source. The article presents a historical and source-oriented commentary on the service of Bishop Jeremiah (Solovyov) to three Russian prelates who were glorified in the 1860's Mitrofan of Voronezh, Demetrius of Rostov, and Tikhon of Zadonsk. The reason for the creation of this hymnographic monument was the intention of the former bishop of Nizhny Novgorod to consecrate one of the churches under construction in honor of these saints. When writing the service to the three saints, Bishop Jeremiah relied on a wide range of sources, including the works of St. Demetrius of Rostov and the penitential canon of Cyril of Turov. The publication is intended to illustrate Bishop Jeremiah's work as a hymnographer and to present a little-known example of a service to Russian saints composed during the Synodal period of the history of the Russian Church.